Hedda Friberg-Harnesk. Reading John Banville through Jean Baudrillard - Ghassemi, Mehdi (ABEI Journal, 2021)
Hedda Friberg-Harnesk. Reading John Banville through Jean Baudrillard. New York: Cambria Press, 2018. pp.223.LCCN 2018027875 | ISBN 9781604979534